Verification of Device Compatibility for Heterogeneous Internet of Things (IoT) Devices - Sukhavasi, Suman; Perumal, Thinagaran; Mustapha, Norwati; Yaakob, Razali; Ahmadon, Mohd Anuaruddin; Yamaguchi, Shingo (Evolution of Information, Communication and Computing System, 2022)
The current advancements in technology with its utilization have improved the better usage of smart objects in a smart home system or smart building. Generally, the interconnection of this large number of heterogeneous devices into a common system leads to an interoperability problem due to its standardization in terms of devices and its protocols, which leads to a challenging task for the joint execution of interoperation. This interoperability problem arises in all existing smart environments, such as smart homes, smart industries, and smart cities. Due to the massive quantity of devices involved to share information in a smart home system, there exists an interoperability problem due to its different data formats and devices. For a typical smart home system having five hundred heterogeneous devices for communication for a joint operation to perform, especially desired tasks or services, leads to compatibility issues. Here in this paper tried to propose an ontology model implementing a use case of a smart home environment for device compatibility, device verification, and the device matching time. To evaluate the device compatibility and verification involved five hundred smart devices for which few devices considered as sensory devices for sensing and remaining as actuating devices. In the present work, the device compatibility is checked on the device properties especially in reducing the device matching time and device verification time using the rules engine, the previous ontology was enhanced as lightweight ontology by only considering the important and minimal properties which are required for the present use case implementation. Finally, we proposed an enhanced lightweight ontology model using semantics to distinguish the compatibility of the devices, as well as a query and rules execution time to match the devices.